The contributions of and challenges faced by developmental Non-Governmental Organisations in Gauteng. - Ozigbo, Obiageri Comfort (My University, 2011)
This research was aimed at establishing the contributions of developmental nongovernmental organisations (NGOs) to social welfare service delivery in Gauteng, South Africa, and to examine the challenges they have faced since the transition from Apartheid social welfare to a developmental welfare paradigm. This study revealed how developmental NGOs function to meet the needs of citizens, especially the marginalised and vulnerable class of the society. It also examined the contributions of developmental NGOs in terms of capacity building, physical infrastructure development and their sustainability. The research was qualitative and exploratory in nature, and a multiple case study design was applied. The research sample of 15 participants was drawn from three developmental NGOs registered with the Department of Social Development, Gauteng, South Africa. Five employees from each developmental NGO were interviewed using a semi-structured interview schedule. A face to face interview was the method of data collection. The data collected was analysed. The main findings showed that there is evidence of positive contributions to capacity building and infrastructural development at the grassroots level. However, funding remains the biggest challenge, which then affects the sustainability of development.
Keywords: Developmental Non-Governmental Organisations; Capacity development; Infrastructural development; Sustainability